NARRATIVE FORMATIONS AND THEIR MANIFESTATIONS IN MODERN ARABIC POETRY (Neo Scientific Peer Reviewed Journal, 2023)
Narrative formations and their manifestations in poetry are consistent with narrative logic and masterpieces of creativity, and through them the student reaches to monitor the features of narrative discourse. However, narration in modern Arabic poetry differs from narration in the discourse of other literary genres. The source of narration in Arabic poetry emanates from the human self and its feelings and feelings through images of creativity. The research deals with the formations of narration in Arabic poetry by analyzing Arabic poetic texts and clarifying the elements of narrative narration and addressing literary critical opinions on this subject and discussing the details of the poetic story, the incident poem, and the poem The personality, the poem of dialogue and the poetic tale. The modern Arabic poem continued to bear its lyrical identity or its lyrical genre, although it represented the formed elements in the structure of the narrative discourse.